A Randomized Controlled Trial of Enhancing Positive Aspects of Caregiving in Thai Dementia Caregivers for Dementia - Pankong, Orawan; Pothiban, Linchong; Sucamvang, Khanokporn; Khampolsiri, Totsaporn (Pacific Rim International Journal of Nursing Research, 2018)
Strengthening the positive aspects of caregiving for dementia caregivers is necessary to minimize their burden. This Thai study examined the effectiveness of a program for enhancing positive aspects of caregiving and subjective well-being among caregivers of older persons with dementia. Seventy two participants were randomly assigned equally into experimental and control groups. The experimental group received the Program for Enhancing the Positive Aspects of Caregiving while the control group received usual care. The experimental program consisted of caregiving self-efficacy enhancement, exploring spirituality, and increasing perceived social support. Data were collected using the Positive Aspects of Caregiving Questionnaire and the Thai General Well-being Schedule and analyzed using descriptive statistics, and the one-way and two-way repeated measure ANOVA. Results showed that the program could significantly increase positive aspects of caregiving among the caregivers at 8, 12 and 20 weeks after program implementation. The program could also significantly increase the subjective well-being of the experimental group at all points of measurement. Results of this study suggest that nurses can apply this program to enhance positive aspects of caregiving and subjective well-being for caregivers of older persons with dementia, however further testing of the program is required.